The Influence of Work Environment, Work Discipline, and Competitive Pressure on Business Laboratory Performance - Aisyah, Mukaromah Siti; Totalia, Salman Alfarisy; Octoria, Dini (Soedirman Economics Education Journal, 2025)
The implementation of learning in higher education is not limited to theoretical activities but also includes practical ones. The Economics Education study program has a business laboratory that serves as a platform for students to demonstrate their performance in managing business units. This study was conducted to examine the influence of the work environment, work discipline, and competitive pressure on the performance of the business laboratory, both partially and simultaneously. A quantitative research approach was chosen for this study. The research population consisted of active students in the Economics Education study program who were assigned as business laboratory practitioners. Proportional sampling was used to determine 142 students as respondents. The research variables were measured using a questionnaire instrument, which was then tested for validity and reliability. Data were analyzed using t-tests and F-tests. Regression analysis with its prerequisite tests was also carried out to predict the influence of the three independent variables on business laboratory performance. The findings reported that the work environment influences business laboratory performance, work discipline influences business laboratory performance, while competitive pressure does not influence business laboratory performance. Furthermore, the work environment, work discipline, and competitive pressure simultaneously influence business laboratory performance.